A qualitative study of the post-treatment experiences and support needs of survivors of lymphoma. (June 2017) - Monterosso, Leanne; Taylor, Karen; Platt, Violet; Lobb, Elizabeth; Krishnasamy, Meinir; Musiello, Toni; Bulsara, Caroline; Stratton, Kendall; Joske, David
Abstract: Purpose: To explore the post-treatment experiences and preferences for follow-up support of lymphoma survivors. Methods: Two focus groups were conducted with 17 participants to explore informational, psychological, emotional, social, practical and physical needs, 6–30 months post-treatment for lymphoma. Perceptions regarding a potential model of survivorship care were also elicited. Results: Thematic content analysis revealed five key themes: Information; Loss and uncertainty; Family, support and post-treatment experience; Transition, connectivity and normalcy, and Person-centred post-treatment care. Participants described a sense of loss as they transitioned away from regular interaction with the hospital at the end of treatment, but also talked about the need to find a "new normal". Establishing post-treatment support structures that can provide individualised information, support, reassurance and referrals to community and peer support were identified as a helpful way to navigate the transition from patient to post-treatment survivor. Conclusions: Participants in our study articulated a need for a flexible approach to survivorship care, providing opportunities for individuals to access different types of support at different times post-treatment. Specialist post-treatment nurse care coordinators working across acute and community settings may offer one effective model of post-treatment support for survivors of haematological malignancies. Highlights: Focus groups with lymphoma survivors explored unmet needs and preferences for follow-up support. Participants indicated a sense of loss when they completed treatment. A common theme was the need to return to normal or a 'new normal'. Supportive survivorship care requires a flexible, tailored approach. Health care professionals could provide individualised information and support when patients finish treatment.